Annual Cost of Patients with Osteoarthritis of the Hip and Knee in France. Issue 4 (December 2014) - Bertin, Philippe; Rannou, Francois; Grange, Laurent; Dachicourt, Jean-Noel; Bruel, Pierre; Emery, Corinne; Grandfils, Nathalie; Taieb, Charles
ABSTRACT Objectives: The economic burden of osteoarthritis [OA] has not recently been evaluated in France. This study aimed to provide a health economic update of the patient costs associated with hip or knee OA treated in the community and in medical, surgical and obstetric care [MSO] and post-acute care and rehabilitation [PAC] hospitals in France. Methods: We analyzed data from the Disease Analyzer® database of medical records collected by a representative sample of French general practitioners in 2009–2010 and from the French medical information system program for public and private hospitals in 2010. Results: In 2010, 90 946 patients were hospitalized in MSOs for hip OA [median age: 75 years] and 84 848 patients for knee OA [median age: 71 years], of whom 44% and 61%, respectively, were transferred to PACs. Up to 94.5% of patients underwent joint replacement. Hospitalization engendered annual costs of €9797 per patient with hip OA and €11 644 per patient with knee OA, that is, a total cost of €1.955 billion for patients hospitalized for hip or knee OA in 2010. A total of 18 976 community patients [mean age: 66 ± 12.7 years] with OA were followed up for 1 year in the Disease Analyzer® database. The annual costs per patient were €715 and €764 for hip and knee OA, respectively, including a cost to the healthcare system of €425 and €454, respectively, that is, an estimated €3.5 billion [€2 billion to the healthcare system] for 4.6 million patients. Conclusion: Patients with OA generate considerable healthcare costs in France.